Understanding Religion, Human Rights, and Conflict: Philosophical and Sociological Perspectives - Permana, Asep Amar (Hanifiya: Jurnal Studi Agama-Agama, 2024)
The purpose of this writing is to know the concepts of religion and human rights, freedom of expression, multiculturalism, conflict and conflict resolution from philosophical and sociological perspectives. The research method used in this writing is library research. The results of this study found that from a philosophical perspective, religion, especially Islam, and human rights both are a unity that has values from God Almighty. While freedom of expression is the right of every individual, and multicultural includes the concept of cultural equality itself, which certainly triggers several conflicts in the form of disputes, then there is a settlement process called conflict resolution. As for the sociological perspective, religion and human rights are social facts, freedom of expression is a manifestation of both, multicultural is a difference from each side whether culture or race, conflict and conflict resolution are social processes and their resolution.